Thermal efficiency in hybrid (Al2O3-CuO/H2O) and tri-hybrid (Al2O3-CuO-Cu/H2O) nanofluids between converging/diverging channel with viscous dissipation function: Numerical analysis - Adnan,; Guedri, Kamel; Raizah, Zehba; Tag-Eldin, Elsayed; Ashraf, Waqas; Khan, Umar; M. Galal, Ahmed (Frontiers in Chemistry, 2022)
Heat transfer and energy storage remain a core problem of the industrialist and engineers. So, the concept of new heat transfer fluids namely nanofluids and hybrid nanofluids were introduced so far. Recently, a new third generation of heat transfer fluids is developed known as Modified Hybrid Nanofluids (MHN) synthesized by ternary nanomaterials and the host fluid. Therefore, the study is conducted to investigate the energy storage efficiency between (Al2O3-CuO-Cu/H2O)mhnf and (Al2O3-CuO/H2O)hnf in the presence of novel viscous dissipation effects. The problem is developed for a channel with stretchable walls via thermophysical attributes of binary and ternary guest nanomaterials and the host liquid. The model is tackled numerically and furnished results for the dynamics most specifically energy storage efficiency in (Al2O3-CuO-Cu/H2O)mhnf. It is examined that third generation of heat transfer fluids (Al2O3-CuO-Cu/H2O)mhnf has high thermal energy storage efficiency than traditional nano and hybrid nanofluids. Therefore, this new insights in the heat transfer would be beneficial and cope the problems of energy storage in the modern technological world.